Food system transformation and implications for Bangladesh - Hossain, Md. Tanjil; Babu, Suresh Chandra (Financial Express, 2021)
According to the recently concluded United Nations Food System Summit 21 (UNFSS21), realignment of food system is needed to achieve the Sustainable Development Goals related to eliminating hunger and malnutrition in all forms, poverty reduction and sustainable management of natural resources. Food systems constitute all the activities and entities that are engaged in ensuring sustainable use and management of natural resources used in food production topost-harvest processes, storage, food markets, processing, food trade, consumption, nutrition, and health outcomes for all participating in the food system. In Bangladesh agriculture plays an important role for rural and economic development and structural transformation. Food system in Bangladesh is transforming rapidly but the direction and the pathways for investment are not clear.